Prevalence, Metabolic Consequences of Non Alcoholic Fatty Liver Disease (NAFLD) and its Association with Microvascular Complications and Ventricular Dysfunction in Patients with Type 2 Diabetes Mellitus - Nihar Ranjan Sahoo; Motij Kumar Dalai; Deepak Kumar Dash; Ganeswar Sethy (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Objective: To study the prevalence of non-alcoholic fatty liver disease (NAFLD) and its association of with microvascular complications and ventricular dysfunction in patients with type 2 diabetes mellitus (T2DM). Methods: In this cross-sectional study, 100 T2DM patients were screened randomly for detection of fatty liver in ultrasonography. Patients with fatty liver (NAFLD group, n = 36) were compared with subjects without fatty liver (non-NAFLD group, n = 64). Detailed clinical, biochemical, and imaging parameters like lipid profile, LFT, fasting plasma glucose, 2-hour post-prandial plasma glucose, HbA1C, fasting insulin, spot urinary albumin/creatinine ratio, and 2-D ECHO (M-mode) were performed. Results: The prevalence of NAFLD was found to be 36%. NAFLD group had significantly higher BMI, WHR, blood pressure, glycemic profile, and lipid parameters compared to non-NAFLD group. HOMA IR was elevated significantly in NAFLD group (3.16 ± 1.96) compared to non-NAFLD group (1.73 ± 1.59). There was significantly higher prevalence of all the diabetes-related microvascular complications and LV diastolic dysfunction in NAFLD patients with higher odds for the occurrence of neuropathy (OR = 4.74; P = 0.001), nephropathy (OR = 3.92; P = 0.003), retinopathy (OR = 5.95; P = 0.002), and LV diastolic dysfunction (OR = 1.84; P = 0.043). Conclusions: NAFLD is significantly associated with various diabetes-related microvascular complications as well as LV diastolic dysfunction in T2DM patients.